Industrial mining trial for polymetallic nodules in the Clarion-Clipperton Zone indicates complex and variable disturbances of meiofaunal communities - Lefaible, Nene; Macheriotou, Lara; Pape, Ellen; Molari, Massimiliano; Haeckel, Matthias; Zeppilli, Daniela; Vanreusel, Ann (Frontiers in Marine Science, 2024)
Following several small-scale benthic disturbance experiments, an industrial polymetallic nodule collector trial was conducted by the company Global Sea mineral Resources (GSR) in their exploration contract area in the Clarion-Clipperton Zone using the pre-prototype vehicle Patania II (PATII). In this study, meiofaunal (i.e., nematode abundance, ASV diversity and genus composition) and environmental (i.e., grain size, total organic carbon/total nitrogen and pigment) properties are compared between disturbance categories (i.e., Pre-impact, Collector Impact and Plume Impact). One week after the trial, proxies for food availability within the Collector Impact sediments were altered with lower total organic carbon (TOC) and pigment (i.e., CPE: sum of Chlorophyll a and phaeopigments) values. Albeit not significant, the observed decrease of nematode abundance and ASV diversity, further indicate the consequences of the removal of the ecologically important surface sediment layer within the PATII tracks. Next to sediment removal, exposed sediments were modified in different ways (e.g., central strips, parallel caterpillar imprints with alternating bands of depressions/ripples and interface patches) and were also subject to heavy collector-induced sediment blanketing. We propose that these cumulative impacts have led to intricate seabed modifications with various levels of disturbance intensity which resulted in the high meiofaunal variability observed. Adjacent nodule-rich areas (i.e., Plume Impact) received considerable levels of sediment deposition (2-3 cm) and were defined by significantly lower food sources (CPE, TOC, carbon to nitrogen ratio) and an observation of meiofaunal enrichment (i.e., higher average nematode abundance and ASV diversity; although statistically non-significant), but mechanisms behind these ecological changes (e.g., suspended material-surface fluxes, passive dispersal of fauna in the plume vs. active upward migration and “viability” of redeposited fauna) remain unresolved. We conclude that complex benthic pressure-response relationships associated with the PATII trial, combined with the high degree of natural spatial and temporal variability in abyssal meiofaunal communities and sedimentary parameters, complicates the quantitative assessment of deep-sea mining associated disturbances.